ANALISIS KESALAHAN SISWA SMP KELAS VII PADA PEMBELAJARAN DARING DALAM MENYELESAIKAN MATERI GARIS DAN SUDUT - Wilan Pistasari; Marchasan Lexbin Elvi Judah Riajanto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The implementation of this research was carried out with the aim of analyzing what mistakes students made when solving line and angle problems through online learning. The type of research used is descriptive and qualitative methods. The subject of the study was 25 students of class VII at one of the SMP Negeri 3 Parongpong for the 2020/2021 academic year. The results obtained by processing analytical data with techniques carried out by calculating the percentage of student errors. The instrument presented to students is in the form of 6 description test questions. From the results of the analysis experienced by students, namely students are not careful in understanding the question of lines and angles, students are not able to describe or solve problems. Thus, it can be concluded that students can answer the questions correctly, but some do not by solving them.